Piezo/triboelectric nanogenerators based on 2-dimensional layered structure materials. (March 2019) - Han, Sang A; Lee, Jaewoo; Lin, Jianjian; Kim, Sang-Woo; Kim, Jung Ho
Abstract: Recently, research on energy harvesting has attracted great attention as a solution to energy depletion and environmental problems due to the use of fossil fuels such as coal, natural gas, and oil. To be precise, harvesting technology converts the energy sources around us such as solar, heat, and mechanical energy into electrical energy. It has the advantage of being able to supply and sustain energy on a permanent basis, rather than being non-renewable, and it is also eco-friendly. Among the various energy harvesting techniques, nanogenerators based on piezoelectric and triboelectric phenomena can generate electrical energy based on mechanical energy sources, which are usually ubiquitous, there are no restrictions due to weather, time, or space, and this technology is also user-friendly. Recently, two-dimensional (2D) materials have been chosen for implementing piezo/triboelectric nanogenerators. The 2D materials have transparency, flexibility, and a high surface-to-volume ratio. Owing to the very low thickness of the atomic unit, a stacking structure using 2D materials can be also made to form a very thin device, which is applicable for insertion into the body or wearable electronic devices. In this review, we summarize the characteristics and research results on piezo/triboelectric energy harvesters based on 2D layered structure materials. Graphical abstract: fx1 Highlights: The characteristics of 2D materials are transparency, flexibility, and high surface-to-volume ratio. With these advantages, 2D materials with piezo/triboelectric potential can be applied as various electronic devices. We summarize the research results on piezo/triboelectric energy harvester based on 2D layered structure materials.